Pengaruh Pengetahuan Akuntansi dan Keterampilan Akuntansi Terhadap Pengelolaan Keuangan Masjid di Kabupaten Kuningan - Hamzah, Amir; Rahmawati, Teti; Rahmasari, Sani; Sumarni, Nani (Universitas Ahmad Dahlan, 2024)
This study aims to explore the impact of accounting knowledge and skills of Mosque Prosperity Council (DKM) administrators on mosque financial management. The research employs a descriptive and verificative method with a quantitative approach, involving 152 respondents from 76 mosques in Kuningan Regency. Data analysis was conducted using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS). The results show that accounting knowledge and skills have a significant positive effect on mosque financial management. Good accounting knowledge enables DKM administrators to accurately record and report financial transactions, and to plan budgets effectively. Accounting skills help in preparing clear and systematic financial reports, monitoring cash flows, and ensuring compliance with financial regulations and audits. Professional and transparent financial management enhances the trust of congregants and donors and strengthens relationships with all stakeholders. This study recommends enhancing the capacity of DKM administrators through continuous accounting training and the use of technology to support more effective and accountable mosque financial management.